FAKTOR YANG MEMPENGARUHI MINAT GEN Z DALAM BERINVESTASI DI PASAR MODAL - Toto, Toto; Kartika, Risna (Universitas Prof. Dr. Hazairin SH, 2023)
This study aims to determine the factors that influence the lack of investing intention in the capital market in students of the Faculty of Economics, Universitas Galuh, based on data from the Faculty of Economics, Universitas Galuh. Based on information from the Academic section, the number of active students in 2022 is 2000, while according to data from the Indonesia Stock Exchange Investment Gallery, data for opening a Customer Fund Account are 100 students. Based on this phenomenon, the author aims to analyze this. The research method used a qualitative approach, namely by using a method that involves more data and information through respondents as subjects who can provide answers to this research. Respondents in this study collected data by obtaining journals related to titles, observing and conducting interviews with students of the Faculty of Economics, Universitas Galuh. Based on the results of the study, there are several things that influence Z Generations investing intention, including technological advances, financial literacy, income, expected return, stock risk and information.